A GATA/homeodomain transcriptional code regulates axon guidance through the Unc-5 receptor - Labrador, Juan; Hulsmeier, Jorn (My University, 2012)
Transcription factor codes play an essential role in neuronal specification and axonal guidance in both vertebrate and invertebrate organisms. However, how transcription codes regulate axon pathfinding remains poorly understood. One such code defined by the homeodomain transcription factor Even-skipped (Eve) and by the GATA 2/3 homologue Grain (Grn) is specifically required for motor axon projection towards dorsal muscles in Drosophila . Using different mutant combinations, we present genetic evidence that both Grn and Eve are in the same pathway as Unc-5 in dorsal motoneurons (dMNs). In grn mutants, in which dMNs fail to reach their muscle targets, dMNs show significantly reduced levels of unc-5 mRNA expression and this phenotype can be partially rescued by the reintroduction of unc-5 . We also show that both eve and grn are required independently to induce expression of unc-5 in dMNs. Reconstitution of the eve - grn transcriptional code of a dMN in dMP2 neurons, which do not project to lateral muscles in Drosophila , is able to reprogramme those cells accordingly; they robustly express unc-5 and project towards the muscle field as dMNs. Each transcription factor can independently induce unc-5 expression but unc-5 expression is more robust when both factors are expressed together. Furthermore, dMP2 exit is dependent on the level of unc-5 induced by eve and grn . Taken together, our data strongly suggests that the eve - grn transcriptional code controls axon guidance, in part, by regulating the level of unc-5 expression
PUBLISHED
PubMed ID: 22461564
Keywords: Transcription factor; Transcription factor